The impact of prior antibiotic use on blood culture and antibiotic susceptibility results in patients with biliary obstruction - Alpaslan Tanoğlu,; Yavuz Beyazıt,; Murat Kekilli, (Turkish Journal of Gastroenterology, 2019)
-